2020
DOI: 10.21608/ejhc.2020.72596
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses' Performance Regarding the Implementation of Patient Safety Measures in Intensive Care Units

Abstract: Background: Nursing surveillance is the key to patient safety as nurses can prevent iatrogenic harm and protect patients in intensive care unit(ICU)from medical errors done by others. Role of critical care nurses in patient safety is influenced by the specific requirements of the specialty which need continuous, close monitoring of the patient, dynamic data analysis and anticipation of complications.Aim of the study: to assess nurses' performance regarding implementation of patient safety in the intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…This findings was in agreement with study conducted by Mamdouh E (2020) (30) who assess nurses' performance regarding the implementation of patient safety measures in intensive care units in Egypt and reported that, the majority of the studied nurses were female. Also Mohamed A (2015) (31) who assess patient safety culture in primary health care services in Alexandria, Egypt and reported that, the majority of the participants were females.…”
Section: Part 1: Sociodemographic Characteristics Of the Studied Nursessupporting
confidence: 92%
“…This findings was in agreement with study conducted by Mamdouh E (2020) (30) who assess nurses' performance regarding the implementation of patient safety measures in intensive care units in Egypt and reported that, the majority of the studied nurses were female. Also Mohamed A (2015) (31) who assess patient safety culture in primary health care services in Alexandria, Egypt and reported that, the majority of the participants were females.…”
Section: Part 1: Sociodemographic Characteristics Of the Studied Nursessupporting
confidence: 92%
“…Medicine error reporting procedures that do not lead to disciplinary action for nurses should be implemented, and patients should be encouraged to report any adverse reactions they may have experienced as a result of the medication. 26,27 Concluded their study as It has been shown that eight methods and twenty-two interventions, mostly with a preventative aim and designed at the hospital level, influencing both the processes and the structural dimensions, are successful in preventing MNC (missed nursing care). Furthermore, 28 discovered that using clustering for nurses' care strategies reduces the spread of infection among nurses and reduces work-related fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Improving nursing performance for patient safety (NPPS) is a crucial, challenging goal for healthcare organizations, particularly regional hospitals striving to achieve patient safety goals. 7 The performance of nurses was developed from their tasks, and contextual performance. 2 Nursing task performance refers to nurses' behavioral contributions to an organization's technical core, encompassing essential duties integral to their roles and providing specialized care, information, support, and coordinating patient care.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%